2013
DOI: 10.1637/10325-081512-case.1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Escherichia coli Isolated from Chickens with Colibacillosis in and Around Harare, Zimbabwe

Abstract: Colibacillosis, a disease caused by avian pathogenic Escherichia coli (APEC), can lead to great economic losses in the poultry industry. The aim of this study was to determine the prevalence of antibiotic resistance and antibiotic resistance patterns in APEC in Zimbabwe. From 503 chickens diagnosed with colibacillosis, 103 E. coli isolates were obtained. Isolation and identification of E. coli were carried out using microscopy and biochemical tests. The disc diffusion method was used to determine antibiotic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
9
21
1
1
Order By: Relevance
“…This finding coincides with the findings of Karczmarczyk, et al, (2011) where resistance to Tetracycline was the highest followed by Cephalothin (cephalosporin), the Amoxicillin. This finding is also partly supported by the findings of Saidi et al, (2012) where E. coli isolates showed moderate rates of resistance to tetracycline and chloramphenicol.…”
Section: Discussionsupporting
confidence: 73%
“…This finding coincides with the findings of Karczmarczyk, et al, (2011) where resistance to Tetracycline was the highest followed by Cephalothin (cephalosporin), the Amoxicillin. This finding is also partly supported by the findings of Saidi et al, (2012) where E. coli isolates showed moderate rates of resistance to tetracycline and chloramphenicol.…”
Section: Discussionsupporting
confidence: 73%
“…These findings are more or less similar to findings of Salehi and Bonab (2006) from Iran who reported similar antimicrobial resistance pattern of avian pathogenic E. coli isolates except that of ampicillin. Regarding the resistance of ampicillin in this study, findings corroborate with the findings of Saidi et al (2013) from Zimbabwe. From the present study, lowest resistance of E. coli isolates was observed to amikacin (25.6%) followed by amoxacillin-sulbactam (31.4%) and gentamicin (32.5%).…”
Section: Discussionsupporting
confidence: 90%
“…4). Saidi et al (2016) showed that there were high prevalence of sensitivity of avian pathogenic E. coli (APEC) to ciprofloxacin (100%) and gentamycin (97.1%). The isolates showed moderate rates of sensitivity to chloramphenicol and neomycin in Harare, Zimbabwe.…”
Section: Antibiotic Sensitivity Testmentioning
confidence: 99%